Arthroscopic Suprapectoral Biceps Tenodesis Using a Standard Suture Anchor Is Safe and Effective - Xavier A. Duralde; Caroline A. Heramb; Jennifer N. Blanda (Arthroscopy, Sports Medicine, and Rehabilitation, 2026)
Purpose To evaluate the safety and efficacy of an arthroscopic technique of suprapectoral biceps tenodesis using a standard absorbable double‐loaded suture anchor. Methods This retrospective study includes all patients who underwent arthroscopic biceps tenodesis by the senior author between December 2017 and June 2020. Biceps tenodesis was performed in patients who had failed conservative management and exhibited evidence of biceps pathology at the time of surgery that appeared to be contributing to the patient's pain. Evaluation criteria included integrity of the repair by physical examination, American Shoulder and Elbow Surgeons score, visual analog scale for pain, and recording any complications and the need for revision surgery. Results A total of 80/96 patients (83%) were available for evaluation at a minimum of 2 years including 43 men and 37 women with an average age of 53 (range 17‐72). Postoperatively, the average in‐office follow‐up was 17 months (range 1.5‐79 months), and the average phone contact follow‐up was 55 months (range 24‐89 months). Ninety‐one percent (73/80) of patients in this series maintained normal biceps contour. The average American Shoulder and Elbow Surgeons score improved from 41 (range: 0‐82) to an average of 83 (range 18‐100) ( P < .001). Visual analog scale pain score improved from 7 (range: 2‐10) to 3 (range: 0‐8) ( P < .001). Minimal clinically important difference thresholds (1.47 for Visual analog scale, 14.3 for American Shoulder and Elbow Surgeons score) were met by 81% and 78.5% of patients, respectively. There were 5 minor complications. Four additional patients complained of pain at the bicipital groove, and a total of 5 patients required revision surgery for either biceps failure or ongoing pain. Conclusions Arthroscopic suprapectoral biceps tenodesis using a standard suture anchor is safe and effective in the management of symptomatic biceps pathology refractory to conservative management. It offers reliable improvements in pain and function while maintaining biceps contour. It has a low complication rate, avoiding many of the potential complications reported after an open approach. Level of Evidence Level IV, retrospective therapeutic study.